FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU HAMIL DALAM PEMENUHAN KEBUTUHAN NUTRISI DI RSIA PERTIWI MAKASSAR - Nurhikmah (Stikes Graha Edukasi Makassar, 2018)
Objective: The purpose of this study is to see what factors are related to the nutritional needs ofpregnant women. Method: In this study used the research design used in this study is cross sectionalthat researchers do observation or measurement of variables at one time. The sample size in thisstudy were 62 respondents who match the inclusion criteria. The data were collected by usingquestionnaires. Results: The results showed that there was a significant relationship betweenknowledge and nutritional needs (p = 0,007), there was a correlation between attitudes withmeaningful nutrition fulfillment (p = 0,000), there was correlation between action and nutritionfulfillment (p = 0,029). Discussion: Behavior is an act or activity of the man himself who has a verywide stretch, among others, walking talking, crying, laughing, working, college, writing, reading, andso forth. Conclusion: there is a relationship between knowledge, attitude with the fulfillment ofnutritional needs. Suggestions: The results of this study can be used as input material to healthpersonnel the importance of monitoring the nutrition during pregnancy in order to reduce the numberof maternal and neonatal deaths